2013
DOI: 10.4049/jimmunol.1300921
|View full text |Cite
|
Sign up to set email alerts
|

Copresentation of Antigen and Ligands of Siglec-G Induces B Cell Tolerance Independent of CD22

Abstract: Differentiation of self from non-self is indispensable for maintaining B cell tolerance in peripheral tissues. CD22 and Siglec-G are two inhibitory co-receptors of the BCR that are implicated in maintenance of tolerance to self-antigens. Enforced ligation of CD22 and the BCR by a nanoparticle displaying both antigen and CD22 ligands induces a tolerogenic circuit resulting in apoptosis of the antigen reactive B cell. Whether Siglec-G also has this property has not be investigated in large part due to the lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 43 publications
1
96
0
2
Order By: Relevance
“…Whether Siglec-G can be induced on the surface of macrophages was not addressed in this study but can easily be done with the new mAb in the future. Our Ab shows a Siglec-G cellular staining pattern very comparable to that of a rat mAb recently discussed in a published paper (20).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Whether Siglec-G can be induced on the surface of macrophages was not addressed in this study but can easily be done with the new mAb in the future. Our Ab shows a Siglec-G cellular staining pattern very comparable to that of a rat mAb recently discussed in a published paper (20).…”
Section: Discussionsupporting
confidence: 78%
“…Our findings are therefore highly relevant for the better understanding of B cell-driven autoimmune diseases and offer new treatment concepts for patients with these diseases. In this context, a Siglec-G ligand-dependent B cell tolerization strategy has been published recently (20).…”
Section: Discussionmentioning
confidence: 99%
“…2A). Because Siglec-G is also expressed on dendritic cells (DCs) (19,21), we analyzed DC numbers in aging mice and also determined activation markers such as MHC class II and CD86 on DCs. We did not detect any significant changes in the three knockout mouse strains (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…For Siglec-G, it was shown that it binds and activates the phosphatase SHP-1, whereas Siglec-10 binds both SHP-1 and SHP-2 phosphatases. These tyrosine phosphatases can dephosphorylate positive regulators of the BCR signaling cascade and cause a dampening of the BCR signal (19,20). Although Siglec-G is expressed on all B cell subsets (19,21), deficiency of Siglec-G in mice causes a strong enlargement of the B1 cell population, but not of B2 cells, indicating that Siglec-G has mainly a B1 cell-restricted inhibitory function.…”
mentioning
confidence: 99%
See 1 more Smart Citation